Less Expansion of Short-Pulse Laser Scars in Panretinal Photocoagulation for Diabetic Retinopathy - Higaki, Masahiko (J Ophthalmol, 2018)
PURPOSE: To compare the expansion rates of laser photocoagulation scars between the conventional laser and short-pulse laser using fundus autofluorescence (FAF). METHODS: Retrospective chart review. Conventional laser was performed on 6 eyes of 6 patients, and short-pulse laser was performed on 11 eyes of 8 patients with diabetic retinopathy. FAF images were obtained by Optos® 200Tx (Optos, Dunfermline, Scotland, UK) at 1, 3, 6, and 12 months after treatment. The average area of 20 photocoagulation scars was measured by using ImageJ software. The expansion rates were calculated from the proportion of the averaged area against the optic disc area. Regression of retinopathy and central macular thickness were also evaluated. RESULTS: The expansion rates of the conventional laser scars compared with the size at 1 month after treatment were 1.12 ± 0.08 (3 M), 1.27 ± 0.12 (6 M), and 1.39 ± 0.11 (12 M). The expansion rates of the short-pulse laser scars were 1.04 ± 0.05 (3 M), 1.09 ± 0.04 (6 M), and 1.13 ± 0.05 (12 M). The expansion rates of the short-pulse laser were significantly lower than those of the conventional laser (p < 0.01). CONCLUSION: FAF images were useful to evaluate the changes in the photocoagulation scar sizes. The scars with the short-pulse laser showed lower expansion rates than those of the conventional laser.